PENGARUH DANA PIHAK KETIGA DAN RASIO KECUKUPAN MODAL TERHADAP PEMBIAYAAN MURABAHAH - Aziz, Kresnhanto; Nurdiansyah, Dian Hakip (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to examine the effect of Third Party Funds and Capital Adequacy Ratio on Murabahah Financing in Indonesia from 2017-2019. This research method uses quantitative approach. The data used in this study comes from financial statements of sharia bank companies in Indonesia for the period of 2017-2019. Then, the data that has been obtained will be analyzed using multiple linear regression analysis and hypothesis testing consisting of the t test and f test with the help from SPSS 23 software. The sampling technique uses non probability sampling with purposive sampling technique. The results of statistical testing show that partially Third Party Funds has positive effect on Murabahah Financing and Capital Adequacy Ratio has positive effect on Murabahah Financing. Meanwhile, simultaneously Third Party Funds and Capital Adequacy Ratio has an effect on Murabahah Financing. Then, the coefficient of determination (R2) was 97,5%. This shows that Third Party Funds and Capital Adequacy Ratio variables can effect the Murabahah Financing by 97,5% and the remaining of 2,5% is influenced by other variables which are not used in this study. Keywords: Third Party Funds, Capital Adequacy Ratio, Murabahah Financing